Recent Advances in the Total Synthesis of Tetramic Acid-Containing Natural Products - Wen-Ju Bai; Chen Lu; Xiqing Wang (Journal of Chemistry)
With incredible bioactivities and fascinating structural complexities, tetramic acid- (TA-) containing natural products have attracted favorable attention among the organic chemistry community. Although the construction of the TA core is usually straightforward, the intricate C3-side chain sometimes asks for some deliberative strategy so as to fulfill an elegant total synthesis. This review mainly covers some exceptional synthetic examples for each type of natural product in recent years, showcasing the great achievements as well as unsettled obstacles in this area, in the hope of accelerating the synthetic and biological investigations for this unique type of natural product.